The Role of Na:K:2Cl Cotransporter 1 (NKCC1/SLC12A2) in Dental Epithelium during Enamel Formation in Mice - Jalali, Rozita; Lodder, Johannes C.; Zandieh-Doulabi, Behrouz; Micha, Dimitra; Melvin, James E.; Catalan, Marcelo A.; Mansvelder, Huibert D.; DenBesten, Pamela; Bronckers, Antonius (Frontiers in Physiology, 2017)
Na+:K+:2Cl− cotransporters (NKCCs) belong to the SLC12A family of cation-coupled Cl− transporters. We investigated whether enamel-producing mouse ameloblasts express NKCCs. Transcripts for Nkcc1 were identified in the mouse dental epithelium by RT-qPCR and NKCC1 protein was immunolocalized in outer enamel epithelium and in the papillary layer but not the ameloblast layer. In incisors of Nkcc1-null mice late maturation ameloblasts were disorganized, shorter and the mineral density of the enamel was reduced by 10% compared to wild-type controls. Protein levels of gap junction protein connexin 43, Na+-dependent bicarbonate cotransporter e1 (NBCe1), and the Cl−-dependent bicarbonate exchangers SLC26A3 and SLC26A6 were upregulated in Nkcc1-null enamel organs while the level of NCKX4/SLC24A4, the major K+, Na+ dependent Ca2+ transporter in maturation ameloblasts, was slightly downregulated. Whole-cell voltage clamp studies on rat ameloblast-like HAT-7 cells indicated that bumetanide increased ion-channel activity conducting outward currents. Bumetanide also reduced cell volume of HAT-7 cells. We concluded that non-ameloblast dental epithelium expresses NKCC1 to regulate cell volume in enamel organ and provide ameloblasts with Na+, K+ and Cl− ions required for the transport of mineral- and bicarbonate-ions into enamel. Absence of functional Nkcc1 likely is compensated by other types of ion channels and ion transporters. The increased amount of Cx43 in enamel organ cells in Nkcc1-null mice suggests that these cells display a higher number of gap junctions to increase intercellular communication.